If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x-5)=9(x-27)
We move all terms to the left:
6(x-5)-(9(x-27))=0
We multiply parentheses
6x-(9(x-27))-30=0
We calculate terms in parentheses: -(9(x-27)), so:We get rid of parentheses
9(x-27)
We multiply parentheses
9x-243
Back to the equation:
-(9x-243)
6x-9x+243-30=0
We add all the numbers together, and all the variables
-3x+213=0
We move all terms containing x to the left, all other terms to the right
-3x=-213
x=-213/-3
x=+71
| -7x-10-15x=22+83 | | 2/5c+4/5c-6=c | | (76-x)+34=90 | | q−52= 4 | | 25/(x+22)=3/x | | 8x-138x^2+102=0 | | 13(y+3)=13y+30 | | 31–3x=1 | | 25/x+22=3/x | | x/32=12/16 | | 2x+4=x-31 | | 9(x+11)=9 | | b-1/4+2b-3/4=b-1/2 | | x^2+5x-2040=0 | | m−1=7 | | ((b-1)/4)+((2b-3)/4)=b-(1/2) | | 2x=(-1/9)x^2 | | ((b-1)/4)+((2b-3)/4)=b-1/2 | | (3x^2)(8x)=0 | | 72=2x-8 | | ((b-1)/4)+(2b-3)/4=b-1/2 | | 7*4^x=89 | | 2(x-3)+5(x-1)=4 | | 5^(3x-1)=24 | | 5^3x-1)=24 | | (10x+30)=(8x-3) | | (4x+16)/(2x+4)=0 | | 2^x=1.03 | | G^2-8g+7=0 | | 7(2-x+9=2 | | (2x+4)/(4x+16)=0 | | (3x+15)+(2x)=90 |